Brain abscesses in children: an Italian multicentre study. Issue 13 (3rd August 2017) - RAFFALDI, I.; GARAZZINO, S.; CASTELLI GATTINARA, G.; LIPRERI, R.; LANCELLA, L.; ESPOSITO, S.; GIANNINI, A. M.; MONTAGNANI, C.; MARSEGLIA, G. L.; PIGNATA, C.; BERNARDI, F.; TOVO, P.-A.; et al.
SUMMARY: Brain abscess is uncommon in paediatric population, but of clinical importance because of significant long-term morbidity and mortality. In this multicentre study, promoted by the Italian Society for Paediatric Infectious Diseases, we retrospectively collected patients aged 0–18 years, with a diagnosis of 'brain abscess'. Seventy-nine children were included; the median age was 8·75 years. As predisposing factor, 44 children had preceding infections. The Gram-positive cocci were mostly isolated (27 cases). Sixty (76%) children underwent a surgical intervention. Intravenous antibiotic therapy was administered in all patients, then switched to oral treatment. Clinical sequelae were recorded in 31 (39·2%) children. Twenty-one of them had a single sequela, of which, the most represented, was epilepsy in nine of them. This study focus the attention on the need to have standardized national guidelines or adequate recommendations on type and duration of antibiotic treatment.